The relationship between self-esteem and body image in adolescent girls - Nanda Aufa Nur Fadiah; Ni Putu Rizky Arnani; Masrifah Masrifah (Jurnal Psikologi Tabularasa, 2024)
ABSTRACTPhysical changes during puberty in the adolescent phase where they pay attention to their appearance. Physical changes in adolescents have a relationship to body image and as an important stage for the development of a positive or negative body image. This study aims to see if there is a relationship between self-esteem and body image in adolescent girls at MAN The method in this study applies a quantitative approach that uses correlational techniques. The location of this research was conducted. The location of this study was conducted in Bangkalan and the participants of this study were adolescent girls who attended MAN. The instrument used in this research is a questionnaire and Likert scale as the scale model. The sampling technique used was incidental sampling and the sample size was 85 adolescent girls. Data collection is done using psychological scales to measure self-esteem and body image. Based on the results of the Pearson Product Moment correlation analysis, 0.000 <0.05 means that there is a significant relationship between self-esteem and body image in adolescent girls. If young women have high self-esteem, the higher the body image owned by young women and vice versa.ABSTRACTPerubahan fisik selama masa puber pada fase remaja yang di mana mereka memberikan atensinya terhadap penampilan. Perubahan fisik pada remaja memiliki keterkaitan terhadap body image dan sebagai tahap yang penting untuk pengembangan body image yang positif atau negatif. Penelitian ini bertujuan untuk melihat apakah terdapat suatu hubungan dari antara self-esteem dengan body image pada remaja putri di Madrasah Aliyah Negeri. Metode pada penelitian ini menerapkan pendekatan kuantitatif yang menggunakan teknik korelasional. Lokasi penelitian ini dilakukan di Bangkalan dan partisipan dari penelitian ini merupakan remaja putri yang bersekolah di Madrasah Aliyah Negeri. Instrumen yang digunakan dalam penelitian ini berupa kuesioner dan skala likert sebagai model skalanya. Teknik penarikan sampel yang dilakukan ialah insidental sampling dan jumlah sampel sebesar 85 remaja putri. Pengumpulan data yang dilakukan adalah menggunakan skala psikologi untuk mengukur self-esteem dan body image. Berdasarkan hasil analisis korelasi Pearson Product Moment dihasilkan 0,000 < 0,05 berarti ada hubungan yang signifikan antara self-esteem dan body image pada remaja putri. Apabila remaja putri mempunyai selfesteem yang tinggi maka akan semakin tinggi body image yang dimiliki oleh remaja putri dan sebaliknya.